Science, Fraud & the Baltimore Case. - Bernstein, Jeremy (Commentary)
Presents information on the scientific discovery of retroviruses. Questions raised by David Baltimore on the particularities of a retrovirus; Mechanism of action of the retroviruses; How Baltimore applied the retrovirus to the immune system of AIDS patients; Views regarding the discovery of retroviruses.